Spectroscopic Characterization and Reactivity of Triplet and Quintet Iron(IV) Oxo Complexes in the Gas Phase - Andris, Erik; Jašík, Juraj; Gómez, Laura; Costas, Miquel; Roithová, Jana (Angewandte Chemie (International ed. in English), 2016)
Closely structurally related triplet and quintet iron(IV) oxo complexes with a tetradentate aminopyridine ligand were generated in the gas phase, spectroscopically characterized, and their reactivities in hydrogen-transfer and oxygen-transfer reactions were compared. The spin states were unambiguously assigned based on helium tagging infrared photodissociation (IRPD) spectra of the mass-selected iron complexes. It is shown that the stretching vibrations of the nitrate counterion can be used as a spectral marker of the central iron spin state.
Keywords: IR spectroscopy; spin state; mass spectrometry; C−H activation; iron complexes